NEGOTIATING THE PAST-IMAGINING THE FUTURE: The Qur’an and the Ritual of Saminism (JOURNAL OF INDONESIAN ISLAM, 2025)
This paper investigates how far the Qur’an penetrated into the ritual of Samin people in Central Java. Taking their conversion to Islam and the politics of religion as point of departure, this paper argues that the attempts of Samin people to negotiate their previous belief to the present involve their unique interpretation of the Qur’an in their religious tradition. For the young Saminist it is a strategy to shape new morality and materiality of being a Muslim. The present ritualistic tradition among Saminist then comes up with complexity; it is by maintaining the locality and adopting the new element for their ritual. Such negotiation was due to massive political project of santrinization in contemporary Indonesia and vast decline of abangan community. In this context, the Qur’an and the produced religious ritual at certain tradition among Saminist are discursive in which the Samin community rationalize the new ritual based on their understanding about Islam rooted on their historical narrative.